Effects of Tongue Force Training on Bulbar Motor Function in the Female SOD1-G93A Rat Model of Amyotrophic Lateral Sclerosis. (February 2017) - Ma, Delin; Shuler, Jeffrey M.; Kumar, Aishwarya; Stanford, Quincy R.; Tungtur, Sudheer; Nishimune, Hiroshi; Stanford, John A.
Background . The use of exercise in amyotrophic lateral sclerosis (ALS) is controversial. Although moderate exercise appears to be beneficial for limb muscles in ALS, the effects of exercise on bulbar muscles such as the tongue have not been studied. Objective . To determine the effects of tongue force training on bulbar motor function in the SOD1-G93A rat model of ALS. Methods . We compared the effects of tongue force training on bulbar motor function and neuromuscular junction innervation in female SOD1-G93A rats and age-matched female wild-type controls. Half of each group underwent afternoon tongue force training sessions, and all rats were tested under minimal force conditions in the mornings. Results . Tongue force did not differ between the SOD1-G93A rats and healthy controls during the morning testing sessions, nor was it affected by training. Surprisingly, decreases in tongue motility, the number of licks per session, and body weight were greater in the tongue force–trained SOD1-G93A rats. Forelimb grip force, survival, and denervation of the genioglossus (GG) muscle did not differ between the trained and untrained SOD1-G93A rats. GG innervation was correlated with changes in tongue force but not tongue motility in SOD1-G93A rats at end stage. Conclusions . The results indicate a potential deleterious effect of tongue force training on tongue motility in female SOD1-G93A rats. The lack of a relationship between GG innervation and tongue motility suggests that factors other than lower–motor neuron integrity likely accounted for this effect.